How Microlet Drivers Sustain Community amid Transportation Transformation - Elisabet Sianturi; Hamsah Hasmah; Nismawati Nismawati (DISCOURSE: Indonesian Journal of Social Studies and Education, 2026)
Changes in the transportation structure and growing competition from app-based transportation have created new pressures on the sustainability of microlet drivers’ communities. Under these conditions, social solidarity becomes important not merely as a form of social cohesion but also as a mechanism through which a community sustains itself amid economic change. This study examines how solidarity is practiced, maintained, and negotiated among microlet drivers in Tataaran II Village, South Tondano District. The study employs a qualitative approach, drawing on data collected through observation, in-depth interviews, and documentation. The data were interpreted using Émile Durkheim’s perspective on social solidarity. The findings demonstrate that solidarity among microlet drivers is grounded in shared occupational identities, common experiences, a sense of shared fate, kinship relations, and social and religious values, all of which are reproduced through everyday practices. Solidarity is further sustained through informal queuing systems at loading points, information exchange, technical assistance when vehicles encounter problems, rotating savings groups, deliberation, and collective social activities. These practices indicate that mechanical and organic solidarity do not necessarily operate as separate forms. Shared identities and experiences provide the basis for collective cohesion, while functional interdependence in organizing work and responding to economic pressures reflects an organic dimension of solidarity. Importantly, competition for passengers and the expansion of app-based transportation do not automatically erode solidarity. Instead, they increase the need for coordination, trust, and mutual support among drivers. The study argues that solidarity functions as an adaptive social mechanism through which microlet drivers manage the tension between individual economic interests and collective sustainability amid the transformation of the transportation sector.